Design and Implementation of a Network Programming Module (A Secure Client-Server Chat Application) - Ukaegbu, Chinedu; Kadiri, Emmanuel (My University, 2023)
Several network systems are built to communicate with one another as well as made available through service-oriented architectures. In this project, the client server architecture is used to develop a chat application. Firstly a chat application is created for both Client and Server which is based on Transmission Control Protocol (TCP) where TCP is connection oriented protocol and is a reliable connection protocol. As security is the key factor while communicating over a network, so in this project, MySQL SSL protocol and hash function was used for the Database based on a numbers of benefits. The hash values of the real password and the random generated number (salt) is stored in the database. The original password is not stored on the system, making cracking of password much harder.
Keywords: Application; Client Server Chat; Network Model; Password Encryption; Port; Protocol TCP